2006
DOI: 10.1007/s00423-006-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclosporin in preventing or delaying colectomy in children with severe ulcerative colitis

Abstract: Treatment with oral CyA altered the course of UC in 28/32 (87%) of patients; 4/32 (13%) did not respond to oral CyA and underwent colectomy. Of the 28 patients that responded to CyA, five underwent later elective colectomy. Overall, in 72% of patients, colectomy was avoided. We, therefore, suggest a trial of oral CyA in all children with severe UC who are dependent or resistant to corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…61 Eight small pediatric cohorts and case series reported the effectiveness of cyclosporine as a salvage therapy in steroid-refractory children with UC with a pooled shortterm success rate (i.e., lack of colectomy) of 81% (95% CI: 76%-86%) but only 39% (29%-49%) in the long term ( Table 2). The long-term success rate was higher in the two studies that introduced immunomodulators at discharge to all patients (pooled rate 71% (55%-83%) 62,63 ). Cyclosporine should only be administered as a bridge to thiopurine treatment; its relatively high toxicity profile (Table 2) dictates that it should be discontinued once thiopurines are effective, typically after 3-4 months.…”
Section: Choice Of Second-line Therapymentioning
confidence: 95%
“…61 Eight small pediatric cohorts and case series reported the effectiveness of cyclosporine as a salvage therapy in steroid-refractory children with UC with a pooled shortterm success rate (i.e., lack of colectomy) of 81% (95% CI: 76%-86%) but only 39% (29%-49%) in the long term ( Table 2). The long-term success rate was higher in the two studies that introduced immunomodulators at discharge to all patients (pooled rate 71% (55%-83%) 62,63 ). Cyclosporine should only be administered as a bridge to thiopurine treatment; its relatively high toxicity profile (Table 2) dictates that it should be discontinued once thiopurines are effective, typically after 3-4 months.…”
Section: Choice Of Second-line Therapymentioning
confidence: 95%
“…36 Pediatric cyclosporine data come from 8 retrospective case series (total of 94 children) in which the rate and adverse events were similar to those reported in adults. 7,37 The pooled short-term response was 81%, but only 39% avoided colectomy in the long-term. 7 Heterogeneity in the definition of disease activity, concomitant therapies, follow-up period (1-5 years), dose, and route of administration (half started with oral therapy) limit interpretation of these combined studies.…”
Section: Figurementioning
confidence: 99%
“…In adults, both IV cyclosporine and oral tacrolimus have also been shown to be effective at inducing remission in IV steroid failure [3538]. The use of IV cyclosporine has not been as successful in small pediatric cohort studies, which demonstrated short benefit with the use of cyclosporine with successful delay of colectomy of 81% of patients in the acute period, but only 39% avoided colectomy at long-term follow-up; and thus with its significant side effect profile including nephrotoxicity, it is not indicated in maintaining remission [24, 39]. …”
Section: Current Therapiesmentioning
confidence: 99%